The Impact of Social Media on the Choice of Dental Implant Treatment - Kuddusi Akbulut; Funda Gökçe Akbulut (European Annals of Dental Sciences)

(untitled)
ABSTRACTPurpose: With the rapid spread of social media use, social media sharing has also become widespread in the field of healthcare. Social media sharing is also actively used in dentistry practices. The aim of this study is to determine the effect of information about dental implant treatment shared on social media on patients' treatment decision processes.Materials and Methods: The study was designed as a web-based survey study. Individuals over the age of 18, who had no previous implant treatment history and who used social media were included.Results: The online survey was conducted on a total of 401 participants, 355 women and 46 men. 41.1% of the participants stated that they first learned about the concept of dental implants from the dentist. A statistical connection was found between age and the social media application used (p=0,001). A statistically significant connection was found between education level and the first source of learning the term dental implant (p=0,044). A statistically significant connection was found between age and the effect of negative comments on social media on fears about implant treatment (p=0,018). A statistically significant connection was found between age and the effect of the brand/country of manufacture of the dental implant on the choice of dental implant (p=0,006).Conclusions: Posts about dental implant treatment on social media have a direct impact on individuals' dental implant decision process. Social media platforms can be recommended to dentists as communication and marketing tools that can bring new patients.